Trypanosoma cruzi in donors who go to the "Dr. Julio Garcia Alvarez" Blood Bank of the Dr. Luis Razetti Hospital, in the Barinas city, Venezuela - Maria del Carmen Barrueta; Carlos Alberto González; Ana María Bolivar (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Trypanosoma cruzi is the causative agent of Chagas disease; this is considered one of the main parasitosis in Latin America. Blood transfusions occupy the second place of transmission of this parasite, after vector transmission and usually occur in urban areas through infected donors from endemic rural areas, generally asymptomatic and ignorant of their condition. In Venezuela, Barinas state is recognized as an important endemic area of T. cruzi transmission. In this sense, was to evaluate parasitological and serological techniques in donors who go to the "Dr. Julio Garcia Alvarez" Blood Bank in the Barinas city. To this end, 240 blood samples were collected from an equal number of donors and were assessed with fresh examination techniques, capillary microcentrifugation, colored smears, and ELISA anti-T. cruzi IgG. In none of the samples circulating parasites were observed, while 3 donors resulted positive with ELISA anti-T. cruzi IgG (1.25% seroprevalence). Direct parasitological tests were not effective for the determination of T. cruzi because there was no evidence of blood trypomastigotes in any of the cases studied.